(untitled) (Journal of Management and Educational Sciences, 2025)
The purpose of this study is to examine the effect of teachers’ job satisfaction levels on organizational presenteeism. The research was conducted on a total of 327 teachers working in the provinces of Izmir, Antalya, and Şanlıurfa during the 2024–2025 academic year. A correlational survey model, one of the quantitative research methods, was used in the study. The Socio-Demographic Information Form, Job Satisfaction Survey, and Organizational Presenteeism Scale were used as data collection tools. The data obtained were analyzed using the SPSS 25.0 software package; descriptive statistics, independent samples t-test, one-way analysis of variance (ANOVA), Pearson correlation, and multiple linear regression analyses were applied. According to the research findings, teachers’ levels of organizational presenteeism were found to be moderate, while their levels of job satisfaction were relatively high. No significant differences were found in job satisfaction and organizational presenteeism scores based on gender, marital status, and education level variables. In contrast, significant differences were found in organizational presenteeism levels based on age and professional experience variables. Regression analysis results showed that some sub-dimensions of job satisfaction (particularly salary, benefits, and coworkers) were significant predictors of organizational presenteeism. However, a low and statistically insignificant relationship was found between overall job satisfaction and organizational presenteeism. In conclusion, it was found that organizational presenteeism behaviors, which limit teachers’ functional performance despite their physical presence in schools, are particularly related to working conditions and perceptions of organizational support. In this context, it is considered that institutional improvements aimed at increasing teachers’ job satisfaction may be effective in reducing presenteeism behaviors.